INFLUENCE OF ROSUVASTATIN ON VASCULAR ENDOTHELIUM FUNCTIONAL STATE AND SYSTEMIC INFLAMMATION IN PATIENTS WITH ISCHEMIC HEART DISEASE AND DIABETES MELLITUS - Fushtey, I. M.; Podsevahina, S. L.; Palamarchuk, O. I.; Tkachenko, O. V.; Kulinich, I. A. (Modern medical technology, 2022)
Purpose of the study. The goal of the present study was to evaluate the effect of low dosed statins (rosuvastatin 10 mg/day) on the state of lipid and carbohydrate metabolism, insulin levels, vascular endothelial function, and markers of systemic inflammation in patients with ischemic heart disease in combination with diabetes mellitus. Materials and research methods. We examined 83 patients with ischemic heart disease and type 2 diabetes mellitus aged 44 to 78 years (mean age was (56,8 ± 3,4) years). For all patients, the fasting glucose level was determined, the HOMA index, the levels of total cholesterol, low density lipoproteins, very low density lipoproteins, high density lipoproteins and triglycerides in the blood, the concentration of C-reactive protein, and the content of pro-inflammatory cytokines in the blood serum were calculated. To study the function of the endothelium, dopplerography of the brachial artery was used according to the D.S. Celermajer. All patients received IHD therapy according to generally accepted standards. The drugs were used against the background of stable oral hypoglycemic therapy. As cholesterol-lowering therapy, rosuvastatin was prescribed at a dose of 10 mg/day for 3 months. Results. During the study, it was noted that in patients with coronary artery disease in combination with type 2 diabetes mellitus on the background of hyperand dyslipidemia, elevated levels of insulin and glucose, dysfunction of the vascular endothelium was revealed. Vascular endothelial dysfunction had a close correlation with markers of systemic inflammation, which was exacerbated by the presence of insulin resistance. While taking rosuvastatin at a dose of 10 mg/day, in addition to a sufficient lipid-correcting effect, there was a decrease in the level of IR, activity of systemic inflammation and improvement in the function of the vascular endothelium, which ensures the correction of additional risk factors in patients with coronary artery disease in combination with type 2 diabetes. Conclusions. In patients with ischemic heart disease in combination with type 2 diabetes mellitus on the background of hyperand dyslipidemia, elevated levels of insulin and glucose, dysfunction of the vascular endothelium was revealed. Dysfunction of the vascular endothelium is closely correlated with markers of systemic inflammation, which is exacerbated by the presence of insulin resistance. Against the background of taking rosuvastatin at a dose of 10 mg/day, in addition to a sufficient lipid-correcting effect, a decrease in the level of IR, activity of systemic inflammation and an improvement in the function of the vascular endothelium were noted, which ensures the correction of additional risk factors in patients with coronary artery disease in combination with type 2 diabetes.